Quantifying the volcanic emissions which triggered Oceanic Anoxic Event 1a and their effect on ocean acidification. Issue 1 (11th December 2016) - Bauer, Kohen W.; Zeebe, Richard E.; Wortmann, Ulrich G.
Abstract: The Cretaceous Oceanic Anoxic Event 1a (Early Aptian) is thought to be causally related to the eruption of the Ontong Java Plateau large igneous province. This study uses osmium isotope records to quantify the magnitude of the respective CO2 emissions up to the onset of Oceanic Anoxic Event 1a, and model the associated changes in carbonate saturation state (Ω), atmospheric pCO2, carbon isotope ratios and the carbonate compensation depth with a carbon cycle model. These model results suggest that volcanism associated with the rapid negative 187/188 osmium ratios observed during the onset of Oceanic Anoxic Event 1a (Selli Event) increased the planetary CO2 degassing flux at least six‐fold, causing a negative δ 13 C excursion of ca 1·5‰ in the dissolved surface ocean inorganic carbon pool. This is consistent with previously published δ 13 C data. Volcanic degassing of this magnitude would also suppress the aragonite saturation state of surface water to near under‐saturated values (Ω ca 1·1 to 0·9), shoal the carbonate compensation depth by 1500 m and increase the atmospheric pCO2 by 3000 p.p.m., before increased weathering and anoxia would counter the pCO2 increase.